2020
DOI: 10.3389/fpls.2020.538311
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Soil Microbiome Profiles in the Companion Planting of White Clover and Orchard Grass Using 16S rRNA Gene Sequencing Data

Abstract: Companion planting is one of the most common and effective planting methods in modern agriculture. White clover (Trifolium repens L.) and orchard grass (Dactylis glomerata L.) are two typical pastures planted together to promote each other's growth. However, the detailed biological foundations of companion planting remain unclear. In this study, we screened typical microbiome profiles under separate and combination planting conditions using 16s RNA gene sequencing techniques. We identified the typical distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…However, Primer 343F/798R is reported to be robust for the amplification of 16s rRNA V3 and V4 fragment (Y. L. Chen et al., 2015; Nossa et al., 2010). Hence, Primer 343F/798R is widely used for microbial samples in marine environments (Lai et al., 2023; Tang et al., 2018) and soils (L. Chen et al., 2020b; H. Li et al., 2019).…”
Section: Evaluation Of the Experimental Approachmentioning
confidence: 99%
“…However, Primer 343F/798R is reported to be robust for the amplification of 16s rRNA V3 and V4 fragment (Y. L. Chen et al., 2015; Nossa et al., 2010). Hence, Primer 343F/798R is widely used for microbial samples in marine environments (Lai et al., 2023; Tang et al., 2018) and soils (L. Chen et al., 2020b; H. Li et al., 2019).…”
Section: Evaluation Of the Experimental Approachmentioning
confidence: 99%
“…Soil microbiome play a crucial role in formation and retaining of soil fertility and quality (De Mandal et al 2019, Abakumov et al 2020, Chen et al 2020, Kui et al 2021, Nikitin et al 2022, which is especially important for severe conditions of agriculture in cryolithozone. The majority of agricultural lands in Russia is concentrated in the European part of the country ( [1] Stolbovoy 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers found that eclectic biological approaches can gain these ends. Microbial agents can substitute for agricultural chemicals, some of which have exhibited notable amelioration to the surrounding environments [2], by providing abundant nutrients to crops and improving soil quality and nutrient cycling [3], and ultimately enhancing crops production [4]. As a type of microbial biological agent, plant endophytes seem to be a veritable biological treasure trove.…”
Section: Introductionmentioning
confidence: 99%